Clinical and molecular evaluation of patients with ovarian cancer in the context of drug resistance to chemotherapy - Opławski, Marcin; Średnicka, Agata; Niewiadomska, Ewa; Boroń, Dariusz; Januszyk, Piotr; Grabarek, Beniamin Oskar (Frontiers in Oncology, 2022)
The present study aimed to evaluate changes in the expression patterns at the gene and protein levels associated with drug resistance. The study group included 48 women who had a histopathologically confirmed diagnosis of stage I-IV ovarian cancer, they were divided into two subgroups (groups A and B). In group A, there were 36 patients in whom surgical treatment was supplemented with first-line chemotherapy according to current standards. Within this patient group, 5 had stage I (14%), 5 had stage II (14%), 25 had stage III (69%), and 1 had stage IV ovarian cancer (3%). Drug resistance was found after the third cycle of chemotherapy in 17 patients (71%) and after the sixth cycle in 7 patients (29%). Group B included 12 women with type I ovarian cancer, including 11 with stage I and 1 patient with stage IV ovarian cancer. The oncological treatment required only surgery. The control group (C) included 50 women in whom the uterus and adnexa were surgically removed for non-oncological reasons. Significantly higher levels of carcinoma antigen 125 CA-125 and human epididymis protein 4 HE4 were observed in group A and in menopausal women. Moreover, drug resistance was associated with significantly higher levels of CA-125 (p < 0.05). The genes UBA2, GLO1, STATH, and TUFT1 were differentiated in test samples from control samples. Moreover, drug resistance was associated with significantly higher expression of GLO1. The results of these assessments indicated the strong link between UBA2 and hsa-miR-133a-3p and hsa-miR-133b; GLO1 and hsa-miR-561-5p; STATH and hsa-miR-137-3p and hsa-miR-580-3p; and TUFT1 and hsa-miR-1233-3p and hsa-miR-2052. Correlation analysis showed a significant correlation between CA-125 and HE4 levels. Moreover, a significant correlation between TUFT1 mRNA and UBA2, GLO1, STATH (negative correlation), and TUFT1 in relation to CA-125 and HE4 (p < 0.05) was noted in all patients. In view of the lack of screening tests for ovarian cancer, the occurrence of the described correlation may be inscribed as an attempt to establish an assay that meets the criteria of a screening test and thus increase the early diagnosis of ovarian cancer.